Bibliographie analytique de l'Afrique antique XLV (2011) - Coltelloni-Trannoy, Michèle; Briand-Ponsart, Claude; Pons Pujol, Lluís; Rocca, Elsa; Villey, Thomas (Bibliographie analytique de l'Afrique antique (BAAA), 2018)
undefined